Uji Kelayakan Jaringan Lokal Universitas Jenderal Soedirman Untuk Implementasi VoIP - Ridwan, Muhamad; Nugraha, Azis Wisnu Widhi; Susilawati, Hesti (Jenderal Soedirman University, 2011)
UNSOED has LAN connection which covers almost all of its units, with minimum bandwidth consupmtionat anaverage of275,318 Kbpsfrom a total of 3 Mbpsso we may apply VoIP system in order to replace voice communication system whichis still using PSTN and PABX. Thereforewe need to know aboutjitter and packet loss ofLAN,and also the codec needs tobedetermined due to voice quality expected and also bandwidth consumpted. Measurementscarried out in two scenariosbased on topologies used in UNSOED (star and ring), in the first scenario (star and ring)server placed on serverfarm meanwhile the second scenario(ring) server placed on Pertanian node. Codec adjusted to the available bandwidth capacity and total of phone number that has to handled. The result show that 0,759 ms jitter obtained from scenario 1 and 0,513ms from scenario 2, both of them included in good category with 0-20 ms of range value, otherwise 0% of packetloss obtained from both scenarios these indicated that LANincluded in good category. There is iLBCcodec with 30 ms packet size which is the mosteconomic on bandwidthcost among G.729, G.711, and iLBC (20 ms), because it cost1995,84Kbpsof total bandwidth usedforhandling 140 phone number. Beside that, it has good voice quality with 4,138996 MOS value. So if we use iLBC (30 ms) codec on the VoIPsystem, there will be still a lot of free bandwidth which can used for other applications, it is about 695,873 Kbps(worst condition) and also get a good-voice quality-VoIP.